Moon cake and other stories - Aiken, Joan; Anderson, Wayne (Hodder Children's Book London, 1998)
Powdered sea-horse, green-glass tree snails and moonbeams: these are the ingredients for Mrs Lallyday Lee's moon cake. Can Tom resist a taste? This collection of short stories also tells of a dancing palm tree, entrancing music and hatching dragons.